Evolution along the Great Rift Valley: phenotypic and genetic differentiation of East African white‐eyes (Aves, Zosteropidae). Issue 21 (12th October 2015) - Habel, Jan Christian; Borghesio, Luca; Newmark, William D.; Day, Julia J.; Lens, Luc; Husemann, Martin; Ulrich, Werner
Abstract: The moist and cool cloud forests of East Africa represent a network of isolated habitats that are separated by dry and warm lowland savannah, offering an opportunity to investigate how strikingly different selective regimes affect species diversification. Here, we used the passerine genus Zosterops (white‐eyes) from this region as our model system. Species of the genus occur in contrasting distribution settings, with geographical mountain isolation driving diversification, and savannah interconnectivity preventing differentiation. We analyze (1) patterns of phenotypic and genetic differentiation in high‐ and lowland species (different distribution settings), (2) investigate the potential effects of natural selection and temporal and spatial isolation (evolutionary drivers), and (3) critically review the taxonomy of this species complex. We found strong phenotypic and genetic differentiation among and within the three focal species, both in the highland species complex and in the lowland taxa. Altitude was a stronger predictor of phenotypic patterns than the current taxonomic classification. We found longitudinal and latitudinal phenotypic gradients for all three species. Furthermore, wing length and body weight were significantly correlated with altitude and habitat type in the highland species Z. poliogaster . Genetic and phenotypic divergence showed contrasting inter‐ and intraspecific structures. We suggest that the evolution of phenotypic characters is mainly driven by natural selection due to differences in the two macro‐habitats, cloud forest and savannah. In contrast, patterns of neutral genetic variation appear to be rather driven by geographical isolation of the respective mountain massifs. Populations of the Z. poliogaster complex, as well as Z. senegalensis and Z. abyssinicus, are not monophyletic based on microsatellite data and have higher levels of intraspecific differentiation compared to the currently accepted species. Abstract : White‐eyes are known as a "great speciator" and form various species over the highland‐lowland mosaic of East Africa. In this contribution, we disentangle evolutionary processes driving phenotypic and genetic uniqueness, including representatives from the East African highlands and its surrounding lowland savannahs (such as Zosterops kulalensis ).